2019
DOI: 10.1002/ecy.2580
|View full text |Cite
|
Sign up to set email alerts
|

Non‐circular home ranges and the estimation of population density

Abstract: Spatially explicit capture–recapture (SECR) models have emerged as one solution to the problem of estimating the population density of mobile and cryptic animals. Spatial models embody assumptions regarding the spatial distribution of individuals and the spatial detection process. The detection process is modeled in SECR as a radial decline in detection probability with distance from the activity center of each individual. This would seem to require that home ranges are circular. The robustness of SECR when ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 17 publications
1
51
0
Order By: Relevance
“…In order to obtain a model with different assumptions, a different distance measure must be tested. In future research, the ecological distance proposed in (Royle et al 2013;Efford 2019) could be used instead. This type of distance requires using cost surface based on some theoretically relevant -but still unknown-spatial covariant.…”
Section: Limitations Future Research and Practical Applicationsmentioning
confidence: 99%
“…In order to obtain a model with different assumptions, a different distance measure must be tested. In future research, the ecological distance proposed in (Royle et al 2013;Efford 2019) could be used instead. This type of distance requires using cost surface based on some theoretically relevant -but still unknown-spatial covariant.…”
Section: Limitations Future Research and Practical Applicationsmentioning
confidence: 99%
“…This detection function has two parameters that are estimated, the probability of capture at the activity center of an individual ( g 0 ) and the spatial scale of detection (σ), the latter of which reflects how rapidly capture probability declines with distance from a trap [ 32 , 33 ]. A default assumption of SCR models is that animal home ranges are approximately circular, but this is often violated in natural populations due to a myriad of factors, such as territoriality, heterogeneous distribution of resources, or movement-restricting landscape features [ 72 , 73 ]. If home ranges are elongated in a particular direction (e.g., because of landscape features that restrict movement, such as canyons or rivers) and traps are deployed primarily along the major axis of animal movement such that the trapping array aligns with the directionality of home ranges, estimated density may be severely biased under the circularity assumption [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…A default assumption of SCR models is that animal home ranges are approximately circular, but this is often violated in natural populations due to a myriad of factors, such as territoriality, heterogeneous distribution of resources, or movement-restricting landscape features [ 72 , 73 ]. If home ranges are elongated in a particular direction (e.g., because of landscape features that restrict movement, such as canyons or rivers) and traps are deployed primarily along the major axis of animal movement such that the trapping array aligns with the directionality of home ranges, estimated density may be severely biased under the circularity assumption [ 72 ]. Our trapping grids were collectively oriented along the direction of Los Alamos Canyon (the x -axis), with minimal trap coverage along the y -axis, and exploratory analyses suggested that animal movement may have been predominantly aligned with the canyon.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For wildlife surveys, the focus is often animal density or abundance, and survey designs ideally minimize the mean square error of density (or abundance) estimators, equal to the square of the bias plus the variance. SCR estimators have been shown to be unbiased under a wide range of detector arrangements (Efford, 2019a; Efford & Boulanger, 2019; Sun et al., 2014) so that designs that maximize the precision of density (or abundance) estimators—or equivalently, minimize the coefficient of variation of the density estimator CV(D̂)—could reasonably be considered optimal (Efford & Boulanger, 2019; Royle et al., 2014).…”
Section: Introductionmentioning
confidence: 99%